2009
DOI: 10.1111/j.1365-2664.2009.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions and the effect of herbivory on Bt‐Brassica napus, Brassica rapa and Lolium perenne

Abstract: Summary1. The probability of a transgenic crop establishing a feral population outside cultivated areas and possibly outcompeting naturally occurring species needs to be assessed to make an ecological risk assessment of the transgenic crop. 2. The interaction between herbivory and competition is thought to determine the ecological success of insect-resistant plants, and this interaction was investigated in a competition experiment with transgenic insect-resistant Bt-Brassica napus, Brassica rapa, Lolium perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The ability of oilseed rape to successfully invade natural habitats is limited principally by the availability of seed germination sites and interspecific plant competition (Crawley et al, 1993(Crawley et al, , 2001Crawley and Brown, 1995;Hails et al, 2006;Damgaard and Kjaer, 2009). Moreover, in controlled sowings into road verges, field margins and wasteland, very few seedlings survived to maturity due to grazing (e.g.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…The ability of oilseed rape to successfully invade natural habitats is limited principally by the availability of seed germination sites and interspecific plant competition (Crawley et al, 1993(Crawley et al, , 2001Crawley and Brown, 1995;Hails et al, 2006;Damgaard and Kjaer, 2009). Moreover, in controlled sowings into road verges, field margins and wasteland, very few seedlings survived to maturity due to grazing (e.g.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…The transgenic crop used in this study was an insect‐resistant Bt‐oilseed rape, Brassica napus L. Oilseed rape is known to form feral populations in natural and semi‐natural habitats, given a certain amount of disturbance (Crawley & Brown, 1995; Pessel et al., 2001). Furthermore, competition experiments have shown that Bt‐oilseed rape may out‐compete insect‐susceptible plants at high herbivore densities (Damgaard & Kjær, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of oilseed rape to successfully invade natural habitats is limited principally by the availability of seed germination sites and interspecific plant competition (Crawley et al, 1993(Crawley et al, , 2001Crawley and Brown, 1995;Hails et al, 2006;Damgaard and Kjaer, 2009). Moreover, in controlled sowings into road verges, field margins and wasteland, very few seedlings survived to maturity due to grazing (e.g., by molluscs) and abiotic stress (Charters et al, 1999).…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%